2015
DOI: 10.2340/16501977-1895
|View full text |Cite
|
Sign up to set email alerts
|

Switch from abobotulinumtoxinA (Dysport®) to incobotulinumtoxinA (Xeomin®) botulinum toxin formulation: A review of 257 cases

Abstract: For patients with conditions commonly treated in dystonia clinics, switching from abobotulinumtoxinA to incobotulinumtoxinA, given at equivalent doses (~4:1 unit ratio) at similar intervals, was effective, well tolerated and achieved cost savings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…77 Recent studies suggest that 1:4 may be more appropriate. 73,78 AE rates are comparable for all three products with conversion ratios of 1:1 for onaBoNT-A and incoBoNT-A; and 1:4 for incoBoNT-A/onaBoNT-A and aboBoNT-A. 68,79 In summary, in terms of a patient-centric approach, all three…”
Section: Maja Reljamentioning
confidence: 87%
“…77 Recent studies suggest that 1:4 may be more appropriate. 73,78 AE rates are comparable for all three products with conversion ratios of 1:1 for onaBoNT-A and incoBoNT-A; and 1:4 for incoBoNT-A/onaBoNT-A and aboBoNT-A. 68,79 In summary, in terms of a patient-centric approach, all three…”
Section: Maja Reljamentioning
confidence: 87%
“…Serotype A toxins appear to be equivalent in terms of outcome, adverse events, and patient preference. 22,39 An open study of rimaBoNT-B for HFS showed similar extent of benefit, but shorter duration. 78 RimabotulinumtoxinB had a higher incidence of burning pain with injection, likely due to its slightly acidic solution.…”
Section: Doses/toxin Selectionmentioning
confidence: 98%
“…Long-term evaluation has yet to identify differences in clinical profile, patient preference, peak response, duration of benefit, or adverse events between the serotype A toxins. 16,22,25,[37][38][39] Type B toxin, (rimabotulinumtoxinB [rimaBoNT-B]) has rarely been studied in blepharospasm. The use of type B toxin may be associated with more pain on injection, as the toxin is packaged in a solution with a slightly acidic pH.…”
Section: Dose and Toxin Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is available as onabotulinumtoxin (Botox; Allergan Ltd, Marlow, Buckinghamshire, UK), abotoulinumtoxin (Dysport) and incobotulinumtoxin A (Xeomin). These preparations are not bioequivalent; the conversion ratios are approximately Dysport 4 U to Xeomin 1 U to Botox 1 U . BTX is injected intradermally, divided into aliquots covering the area affected.…”
mentioning
confidence: 99%